Rheology fundamentals - Malkin, Aleksandr I︠A︡kovlevich (ChemTec Pub., 1994)
Most technological improvements are realized through application of rheology used to modify properties of materials. At the same time, rheology is a complex discipline not fully understood by most researchers and engineers. It is not because rheology is too difficult to understand but mostly because the discipline uses its own language full of terms and models, understood by rheologists but not commonly used by others. ChemTec Publishing introduces a new series entitled Fundamental Topics in Rheology, designed to facilitate conversion of rheology from a field familiar to a narrow group of specialists to a popularly applied science.
Keywords: Rheology.; elektronické knihy; electronic books